2022
DOI: 10.3389/fgene.2022.919856
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and Diversity of miR166 Family Members From Highbush Blueberry (Vaccinium corymbosum) and Their Potential Functions in Abiotic Stress

Abstract: MicroRNA166 (miR166) is highly conserved and has diverse functions across plant species. The highbush blueberry (Vaccinium corymbosum) genome is thought to harbor 10 miRNA166 loci (Vco-miR166), but the extent of their evolutionary conservation or functional diversification remains unknown. In this study, we identified six additional Vco-miR166 loci based on conserved features of the miR166 family. Phylogenetic analyses showed that mature Vco-miR166s and their precursor cluster in several clades are evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Therefore, our experiment used the coding region sequence to predict miRNA target sites, and we discovered that dof-miR-384 belongs to the miR166 family. The expression level of miR166 is downregulated under drought stress [ 55 ]. In this experiment, dof-miR-384 could bind seven PEPC genes, including Dc_gene2609 , which exclusively showed a significant increase in expression after drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our experiment used the coding region sequence to predict miRNA target sites, and we discovered that dof-miR-384 belongs to the miR166 family. The expression level of miR166 is downregulated under drought stress [ 55 ]. In this experiment, dof-miR-384 could bind seven PEPC genes, including Dc_gene2609 , which exclusively showed a significant increase in expression after drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the miR396-GRF-GIF-SWI/SNF module played an essential role in GA signaling to control plant growth [ 50 ]. In addition, the miR166e/calmodulin-like protein module was newly identified in our research, and the miR166 has been revealed to be involved in salt stress response [ 51 ] and GA biosynthesis and catabolism [ 52 ]. Furthermore, calmodulin-like (CML) proteins, such as Ca 2+ sensors, play important roles in the regulation of plant development and stress responses [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In apples, MIR156a overexpression weakens salt resistance [ 19 ]. The knock-down of miR166 can enhance abiotic stress resistance [ 20 ]. The overexpression of MIR319b and miR319 in the target simulated form (MIM319) demonstrated that miR319 positively regulates salt tolerance in switchgrass [ 21 ].…”
Section: Introductionmentioning
confidence: 99%